EFEKTIVITAS MEDIA PEMBELAJARAN PUZZLE HURUF TERHADAP KEMAMPUAN MEMBACA SISWA KELAS II SD INPRES LEMOA KAB. GOWA - Salmawati; Cayati; Baharuddin Hafid; Jusmawati (STKIP Subang, 2024)
This research was conducted to determine the effectiveness of letter puzzle learning media on the reading ability of class II students at SD Inpres Lemoa district. Gowa. This research uses a quantitative approach with a pre-experimental design research type and a One Group Pretest-posttest design research design. The sampling technique in this research was total sampling. The sample in this research was class II consisting of 11 students consisting of 7 boys and 4 girls. The research instruments used were teacher and student activity observation sheets, reading ability assessment sheets, teacher and student questionnaires, reading tests and documentation as well as data collection techniques consisting of observations, questionnaires, tests and documentation which were reviewed based on students' reading abilities. After analyzing the data, the researcher found the effectiveness of the letter puzzle learning media through three indicators of effective learning, namely for student activity in the letter puzzle learning media 2.5 (Good), student responses with a value of 3.4 (Good) and learning outcomes for the puzzle learning media letter 3.6 (Very Good). So, through the results of the data analysis that has been carried out, it can be concluded that the letter puzzle learning media has proven to be quite effective in the reading ability of students at SD Inpres Lemoa district. Gowa with a score of 3.2 (Quite Effective).